2009
DOI: 10.1103/physrevlett.102.137202
|View full text |Cite
|
Sign up to set email alerts
|

Domain Wall Spin Torquemeter

Abstract: We report the direct measurement of the non-adiabatic component of the spin-torque in domain walls. Our method is independent of both the pinning of the domain wall in the wire as well as of the Gilbert damping parameter. We demonstrate that the ratio between the non-adiabatic and the adiabatic components can be as high as 1, and explain this high value by the importance of the spin-flip rate to the non-adiabatic torque. Besides their fundamental significance these results open the way for applications by demo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
66
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 95 publications
(75 citation statements)
references
References 27 publications
7
66
2
Order By: Relevance
“…SIA results from the presence of AlO x and Pt on either side of the Co layer, where Pt/Co hybridization enhances atomic SO coupling and both interfaces create a strong out-of-plane electron potential gradient. Measurements of the magnetic anisotropy energy and orbital magnetization of Co/Pt [88][89][90], the AHE as well as the enhanced non-adiabatic spin torque component found in Pt/Co/AlO x DW constrictions [76] indicate that SO coupling in such a system is strong. Most importantly, the Co layer is FM at room temperature with 100 per cent remanence, as shown in figure 5b.…”
Section: (D) Spin-orbit Torques In Ultrathin Metal Filmsmentioning
confidence: 99%
“…SIA results from the presence of AlO x and Pt on either side of the Co layer, where Pt/Co hybridization enhances atomic SO coupling and both interfaces create a strong out-of-plane electron potential gradient. Measurements of the magnetic anisotropy energy and orbital magnetization of Co/Pt [88][89][90], the AHE as well as the enhanced non-adiabatic spin torque component found in Pt/Co/AlO x DW constrictions [76] indicate that SO coupling in such a system is strong. Most importantly, the Co layer is FM at room temperature with 100 per cent remanence, as shown in figure 5b.…”
Section: (D) Spin-orbit Torques In Ultrathin Metal Filmsmentioning
confidence: 99%
“…[11][12][13][14] Miron et al reported current-driven DW velocities approaching 400 m/s in Pt/Co/AlOx stacks, 6 much larger than expected from STT alone and in a direction opposite to the electron flow. They attributed these results to a large out-of-plane effective field of ~80 Oe per 10 11 A/m 2 , 15 augmented by a SOC-mediated transverse Rashba field 16 thought to stabilize the Bloch DWs such that they moved rigidly 17 rather than by precession. Evidence for a large current-induced transverse field has been independently confirmed in Pt/Co/AlOx 16,18 and Ta/CoFeB/MgO, 19 but highly efficient current-driven DW motion has not yet been reported in any metal/oxide structure beyond Pt/Co/AlOx.…”
mentioning
confidence: 99%
“…In particular, studies on Co/Pt multilayers show a large nonadiabaticity factor ␤. 7,17,18 The microscopic origin of this large value is still under debate.…”
mentioning
confidence: 99%